Chronic pain syndrome: Pathogenesis, clinical presentation, treatment - A. Yu. Suvorov (Klinicist, 2014)
The paper considers main ideas on the prevalence, course, and therapy of chronic pain syndrome. It describes its manifestations, different course variants, and approaches to treating the diseases accompanied by chronic pain. Different approaches to long-term therapy, which involve combination treatment options, are discussed. Data on the use of nonsteroidal antinflammatory drugs as the most common agents to relieve both acute and chronic pain syndrome are given in detail. The data of numerous trials evaluating both the analgesic and anti-inflammatory effects of nonsteroidal anti-inflammatory drugs are presented.